Agricultural transformation and food and nutrition security in Ghana: Does farm production diversity (still) matter for household dietary diversity? - Ecker, Olivier (Elsevier, 2018)
Africa south of the Sahara experienced an acceleration of economic growth in recent years that was accompanied by structural changes in national economies. Some African countries, such as Ghana, managed to utilize rapid growth for poverty reduction and improving food and nutrition security. Transformation of agriculture appears to have played an important role in this context. However, the linkages between agricultural transformation and food and nutrition security at the household level are not well understood. This article examines the linkage between farm production diversity and household dietary diversity in rural Ghana and how that linkage changed between 2005–06 and 2012–13. The empirical analysis employs a regression model that controls for region- and time-fixed effects. The estimation results suggest that farm production diversification, as well as household income growth, continues to be strongly associated with increased household dietary diversity. The analysis further explores the mechanism that underlies this production-consumption linkage by systematically modifying the basic model specification.